Sięganie nieśmiertelności w interpretacji o. Pawła Fłorenskiego w Мнимости в геометрии [Mnimosti w geometrii] - Kotkowska, Elżbieta (Poznańskie Studia Teologiczne, 2022)
Father Paweł Fłorenski represents an integral worldview based on the Christian and Greek paradigmatic cultural pattern. He was convinced that the knowledge contained in intellectus fidei leads to certain knowledge, although it cannot be complete knowledge. In his opinion, it is possible to get to know the whole through its parts, albeit imperfectly. The basic assumption of Fłorenski’s concept is the statement: one should philosophize only in the religion, penetrating its interior. As a theologian and philosopher, he faced the incomprehensible Mystery and has given it credibility just as a mystery. He used his great erudition and mathematical and technical education. The article is an attempt to present Paweł Fłorenski’s reasoning, describe his rational reasons for the religious truth, that man in his here and now, with the strength of his spirit, has access to the Heaven, in which he fully experiences own immortality. We showed how the Russian theologian, in his courageous thinking, according to the whole, combined data from various areas, i.e., Dante’s poetic vision with the mathematical formalism of Einstein’s theory, to justify the truth of the Christian faith about the human immortality.